2016
DOI: 10.1002/eji.201646393
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node biopsy analysis reveals an altered immunoregulatory balance already during the at‐risk phase of autoantibody positive rheumatoid arthritis

Abstract: The balance between proinflammatory and regulatory CD4+ T cells is tightly controlled in lymphoid organs. In autoimmune diseases this balance is altered in the periphery and target tissue of patients. However, not much is known about the balance initiated in lymphoid organs during the development of disease. Since systemic autoimmunity is present years before the clinical manifestations of rheumatoid arthritis (RA), it is possible to study the immunoregulatory balance during the earliest (preclinical) phases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
25
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 42 publications
11
25
0
1
Order By: Relevance
“…Moreover, another study in mice, in which FRCs were conditionally depleted, showed that attraction and retention of naïve CD8+ T cells was dependent on CCL19 and CCL21 expressing FRCs, while retention of activated CD8+ T cell was regulated otherwise 62 . Interestingly, our results are in line with our previous findings on changes in frequency and activation state of lymphocyte populations within LNs of RA-risk and RA patients when compared with healthy controls 63 65 . RA(-risk) patients have a decreased frequency of lymph node CD4+ CD45RA+ naïve T cells as well as a lower frequency of CCR7 expressing CD4+ and CD8+ T cells in comparison to healthy controls 63 , 64 , which is in line with the decreased capacity to produce CCL19 by LNSCs during the earliest phases of RA.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, another study in mice, in which FRCs were conditionally depleted, showed that attraction and retention of naïve CD8+ T cells was dependent on CCL19 and CCL21 expressing FRCs, while retention of activated CD8+ T cell was regulated otherwise 62 . Interestingly, our results are in line with our previous findings on changes in frequency and activation state of lymphocyte populations within LNs of RA-risk and RA patients when compared with healthy controls 63 65 . RA(-risk) patients have a decreased frequency of lymph node CD4+ CD45RA+ naïve T cells as well as a lower frequency of CCR7 expressing CD4+ and CD8+ T cells in comparison to healthy controls 63 , 64 , which is in line with the decreased capacity to produce CCL19 by LNSCs during the earliest phases of RA.…”
Section: Discussionsupporting
confidence: 93%
“…For the presently investigated ACPAs, we hypothesize that multiple T cell-dependent selection processes with somatic Ig mutations may happen sequentially, for example, in germinal center-like structures located in mucosal tissues, in lymphoid organs, and in joints. Such germinal center-like structures have previously been described in these sites in RA patients (32)(33)(34)(35)(36). In addition, there are indications that immune responses toward citrullinated antigens may be initiated in mucosal tissues, for example, in the lungs.…”
Section: Discussionmentioning
confidence: 68%
“…Peptide ELISAs were performed as previously described (20), with some minor modifications. The ELISAs assessed binding to both citrulline-containing and arginine (Arg)-containing peptides, including filaggrin, α-enolase, vimentin, fibrinogen, and histones H4 , H4 [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] , and H3 . All peptides assessed by ELISA are described in further detail in Supplementary Table 1, available on the Arthritis & Rheumatology web site at http://onlinelibrary.wiley.com/doi/10.1002/ art.40699/abstract.…”
Section: Methodsmentioning
confidence: 99%
“…Th1 mediated immunity may also be relevant in early RA; studies have demonstrated that the preclinical phase of RA is dominated by Th1‐associated cytokines and chemokines (IFN‐γ, IL‐12, and CXCL10) . Moreover, lymph node biopsies taken from individuals with an increased RA‐risk (that is, IgM‐RF and/or ACPA positive individuals with arthralgia but without any evidence of arthritis) and from patients with early RA showed elevated levels of T cells with a Th1 profile (CXCR3+ CCR6− CCR4−) as compared to healthy controls, whereas no such differences were found for T cells with a Th17 or Th2 profile . In established RA, however, the presence of Th1 cells seems to be associated with disease protection rather than exacerbation.…”
Section: Discussionmentioning
confidence: 99%